Platelet Membrane-Coated Nanoparticles Sebagai Sistem Penghantaran Aspirin Daninhibitor P2Y12 Pada Penatalaksanaan Infark Miokard Akut : A Literature Review - Muhammad Rifqi Al Azim; Fawwaz M Virajati; Saminur Muzaqi; Muhammad Althariq Huda (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Acute myocardial infarction (AMI) is a severe manifestation of coronary artery disease, commonly caused by atherosclerotic plaque rupture and thrombus formation. Dual antiplatelet therapy with aspirin and P2Y12 inhibitors is a cornerstone of AMI management but remains limited by bleeding risk and nonspecific drug distribution. Platelet membrane-coated nanoparticles (PM-NPs) are biomimetic drug delivery systems with potential for targeted therapy. Objective: To review the potential of PM-NPs for delivering aspirin and P2Y12 inhibitors in AMI management. Methods: A literature review was conducted using PubMed, ScienceDirect, and Google Scholar with the keywords “platelet membrane-coated nanoparticles,” “aspirin,” “P2Y12,” and “acute myocardial infarction.” Articles published within the last 10 years, available in full text, and written in English or Indonesian were selected according to predefined criteria. Twelve relevant articles were identified after screening. Results: PM-NPs demonstrated potential for targeting thrombi, atherosclerotic plaques, and injured myocardial tissue. They may improve drug stability, circulation time, and targeted delivery while reducing oxidative stress, inflammation, and ischemia-reperfusion injury. However, evidence regarding combined aspirin and P2Y12 inhibitor delivery remains limited and predominantly preclinical. Conclusion: PM-NPs represent a promising targeted antithrombotic platform for AMI. Further studies are required to establish the safety and efficacy of combined aspirin and P2Y12 inhibitor delivery.